In vitro effects of some metal ions on glutathione reductase in the gills and liver of Capoeta trutta - M. Kirici; M. Atamanalp; M. Kirici; Ş. Beydemir (Regulatory Mechanisms in Biosystems, 2017)
Many aquatic environmental problems have arisen in consequence of contamination of water by toxic metals and organic pollutants in the present age of technology. Metals play vital roles in enzyme activities and other metabolic events due to their bioaccumulative and nonbiodegradable properties among aquatic pollutants. The aim of this study was to evaluate the inhibitory effects of some metal ions (Ag+, Cu2+, Co2+, Ni2+, Pb2+ and Zn2+) on Capoeta trutta gill and liver glutathione reductase (EC: 1.8.1.7; GR). For this purpose, initially, GR was purified from C. trutta gill and liver. Purification procedure consisted of three steps; preparation of hemolysate, ammonium sulphate precipitation and 2’, 5’-ADP Sepharose 4B affinity chromatography. Using this procedure, C. turtta gill GR, having the specific activity of 19.111 EU/mg proteins, was purified with a yield of 38.8% and 910.05-fold; C. trutta liver GR, having the specific activity of 16.167 EU/mg proteins, was purified with a yield of 21.1% and 734.86-fold. The purity of the enzymes was checked on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and each purified enzyme showed a single band on the gel. In addition, inhibitory effects of some metal ions (Ag+, Cu2+, Co2+, Ni2+, Pb2+ and Zn2+) on GR from gill and liver were investigated in vitro. Ki constants and IC50 values for metal ions which showed inhibition effects were determined by Lineweaver-Burk graps and plotting activity % vs. [I]. In conclusion, IC50 values for fish gill GR were 0.000625, 0.153, 0.220, 0.247 and 0.216 mM and Ki constants for fish gill GR were 0.00045 ± 0.00008, 0.128 ± 0.036, 0.182 ± 0.138, 0.482 ± 0.219 and 0.112 ± 0.047 mM for Ag+, Cu2+, Co2+, Ni2+, Pb2+ and Zn2+, respectively. IC50 values for fish liver GR were 0.000437, 0.217, 0.185, 0.355 and 0.349 mM and Ki constants for fish liver GR were 0.00025 ± 0.00013, 0.532 ± 0.146, 0.123 ± 0.066, 0.093 ± 0.020 and 0.151 ± 0.084 mM for Ag+, Cu2+, Co2+, Ni2+, Pb2+ and Zn2+, respectively. In vitro inhibition rank order was determined as Ag+ > Co2+ > Zn2+ > Ni2+ > Pb2+ for fish gill GR; Ag+ > Cu2+ > Co2+ > Pb2+ > Ni2+ for fish liver GR. From these results, we showed that Ag+ metal ion is the most potent inhibitor of GR enzyme on gill and liver tissues.